PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) UNTUK MENDUKUNG ASSESSMENT DALAM PEMBELAJARAN BERDIFERENSIASI BAGI GURU DI KOTA SEMARANG - Dewi Nilam Tyas; Sri Sukasih; Desi Wulandari; Eem Munawaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract The implementation of differentiated learning in Gugus Kemuning Semarang City is less than optimal, one of the reasons is the minimal use of AI (Artificial Intelligence) in the assessment process. So it takes quite a long time to be able to find out the results and analysis of the assessment so that it can be interpreted and followed up. The purpose of this activity is to improve understanding and skills in utilizing AI for assessment in differentiated learning. Limited devices and the prohibition on bringing smartphones to school make their utilization less than optimal. To overcome these obstacles, the platform used in this activity is Quizizz paper mode because students only need to hold the QR code that will be scanned by the teacher. The subjects of this activity were 53 teachers of Gugus Kemuning teacher working group. The stages of implementing the activity include: 1) planning, 2) socialization of assessment principles and utilization of AI in compiling assessment instruments, 3) mentoring the development and presentation of the developed assessment instruments, 5) post-test. Based on the activities that have been carried out, it is known that there has been an increase in knowledge and skills in the use of AI for assessment in differentiated learning, as evidenced by the fact that 82% of participants were able to develop assessments by synchronizing learning plans, implementation and assessments and compiling assessment instruments to be more interesting and interactive using Quizizz. Abstrak Pelaksanaan pembelajaran berdiferensiasai di Gugus Kemuning Kota Semarang kurang optimal, salah satunya karena minimnya penggunaan AI (Artificial Intelligece) dalam prose penilaian. Sehingga diperlukan waktu yang cukup lama untuk dapat mengetahui hasil dan analisis penilaian untuk dapat diinterpretasikan dan ditindaklanjuti. Tujuan dari kegiatan ini adalah meningkatkan pemahaman dan keterampilan pemanfaatan AI untuk penilaian dalam pembelajaran berdiferensiasi. Keterbatasan gawai dan larangan membawa smartphone ke sekolah menjadikan pemanfatan AI kurang optimal. Untuk mengatasi kendala tersebut, maka platform yang digunakan dalam kegiatan ini adalah Quizizz paper mode karena peserta didik cukup memegang QR code yang akan dipindai guru. Subjek kegiatan ini adalah 53 guru-guru KKG gugus Kemuning. Tahpan pelaksanaan kegiatan meliputi: 1) perencanaan, 2) sosialisasi prinsip assessment dan pemanfaatan AI dalam penyusunan instrumen assessment, 3) pendampingan pengembangan dan presentasi instrument assessmen,, 5) post test. Berdasarkan kegiatan yang telah dilaksanakan, diketahui bahwa terjadi pengingkatan pengetahuan dan keterampilan dalam pemanfaatan AI untuk assessment dalam pembelajaran berdiferensiasi, dibuktikan bahwa 82% peserta mampu mengembangkan assessment dengan mensinkronkan rencana, pelaksanaan dan penilaian pembelajaran serta menyusun instrumen penilaian menjadi lebih menarik dan interaktif dengan menggunakan Quizizz.